Late Adolescent Decision-Making Style Concerning Academic Achivement - Ivana BULOG; Luka DADIC (Communications of International Proceedings, 2020)
This paper targets the late stage of adolescence by observing decision-making styles among young adults-university students. The main research goal was to evaluate the late adolescent decision-making styles in terms of their academic achievement. The study comprises 77 final-year students on the Croatian Faculty of Economics, Business, and Tourism-University of Split. The results revealed that intuitive decision-making style is the dominant decision-making style among university students. Findings show a negative statistically significant association between dependent, avoidant, and spontaneous decision-making styles with objective and subjective academic achievement variables. However, results indicate that students prone to rational decision-making are positively associated with their academic achievement level. Further, female students are found to show a greater tendency toward intuitive and spontaneous decision-making than male students. Lastly, research results and limitations of the study regarding future research directions are provided.
Keywords: University Students; Decision-Making Style; Academic Achievement.